German and Austrian occupant literature on the Sami in Norway and Lapland – “Harmless” minority, a resource, and well-off “reindeer kings” - Nyyssönen, Jukka (Registered Association of Hela Researchers, 2020)
In previous research on the history of the Second World War in Finland and Norway, relations between the German and Austrian occupying forces and the Sami people have generally been considered to be good. The occupant gaze upon the Sami has been interpreted as exoticizing and “touristic”. Historical encounters and the Sami position in the literary discourse are discussed and explained in this article, using a selection of German and Austrian wartime and post-war literature. The discursive reading the sources bear evidence of multiple ways of relating to the Sami, from benign to racializing; from demeaning to one filled with surprise at unveiling a well-off, yet “primitive” minority. The Sami were positioned in a complex way in the Nazi racial hierarchies, which were multiple, some aspects of which appeared to enable the occupants to posit a benign gaze upon the minority. The authors echoed Nordic research on the Sami, and the hierarchies produced there as well. The weight that race had on perceptions of the Sami is discussed, whilst other socio-economic factors are analysed as well.